Soil temperature, microbial biomass and enzyme activity are the critical factors affecting soil respiration in different soil layers in Ziwuling Mountains, China - Qu, Ruosong; Liu, Guanzhen; Yue, Ming; Wang, Gangsheng; Peng, Changhui; Wang, Kefeng; Gao, Xiaoping (Frontiers in Microbiology, 2023)
Soil microorganisms are critical biological indicators for evaluating soil health and play a vital role in carbon (C)-climate feedback. In recent years, the accuracy of models in terms of predicting soil C pools has been improved by considering the involvement of microbes in the decomposition process in ecosystem models, but the parameter values of these models have been assumed by researchers without combining observed data with the models and without calibrating the microbial decomposition models. Here, we conducted an observational experiment from April 2021 to July 2022 in the Ziwuling Mountains, Loess Plateau, China, to explore the main influencing factors of soil respiration (RS) and determine which parameters can be incorporated into microbial decomposition models. The results show that the RS rate is significantly correlated with soil temperature (TS) and moisture (MS), indicating that TS increases soil C loss. We attribute the nonsignificant correlation between RS and soil microbial biomass carbon (MBC) to variations in microbial use efficiency, which mitigates ecosystem C loss by reducing the ability of microorganisms to decompose organic resources at high temperatures. The structural equation model (SEM) results demonstrate that TS, microbial biomass, and enzyme activity are crucial factors affecting soil microbial activity. Our study reveals the relations between TS, microbial biomass, enzyme activity, and RS, which has important scientific implications for constructing microbial decomposition models that predict soil microbial activity under climate change in the future. To better understand the relationship between soil dynamics and C emissions, it will be necessary to incorporate climate data as well as RS and microbial parameters into microbial decomposition models, which will be important for soil conservation and reducing soil C loss in the Loess Plateau.